A new type of polymer carbon dots with high quantum yield: From synthesis to investigation on fluorescence mechanism. (5th May 2017) - Tao, Songyuan; Song, Yubin; Zhu, Shoujun; Shao, Jieren; Yang, Bai
Abstract: Carbon dots (CDs) is an area of intense focus, currently limited to unclear photoluminescence (PL) mechanism. Much effort has been made to clarify the certain PL centers but is still fruitless. Herein, a new type of polymer carbon dots (PCDs) with absolute quantum yield as high as 44.18% was synthesized by hydrothermally crosslinking polyacrylic acid and ethylenediamine. Through carefully comparing and analysing, the PL centers were supposed to be -NO and -CO (mainly amide and/or its derived structures) rather than large-scale conjugated structure, which was similar to the previously reported sub-fluorophores. Besides, the function of polymer chains was considered to decrease the motion freedoms and provide a solvation effect by crosslinking and wrapping the fluorescence centers, which led to the improved quantum yield and red-shifted emission. The investigation on fluorescence mechanism can provide with a new understanding on crosslink enhanced emission (CEE) effect in non-conjugated fluorescence systems. Graphical abstract: Highlights: A new type of polymer carbon dots was synthesized with QY as high as 44.18%. Crosslinking and immobilizing by polymer chains led to improved QY. The new chemical environment around PL centers led to red-shifted emission. Enrich the content of crosslink enhanced emission (CEE) effect. Provide with a new understanding on the fluorescence of non-conjugated systems.